Spinal Excitability Changes after Transspinal and Transcortical Paired Associative Stimulation in Humans - Maria Knikou (Neural Plasticity)
Paired associative stimulation (PAS) produces enduring neuroplasticity based on Hebbian associative plasticity. This study established the changes in spinal motoneuronal excitability by pairing transcortical and transspinal stimulation. Transcortical stimulation was delivered after (transspinal-transcortical PAS) or before (transcortical-transspinal PAS) transspinal stimulation. Before and after 40 minutes of each PAS protocol, spinal neural excitability was assessed based on the amplitude of the transspinal-evoked potentials (TEPs) recorded from ankle muscles of both legs at different stimulation intensities (recruitment input-output curve). Changes in TEPs amplitude in response to low-frequency stimulation and paired transspinal stimuli were also established before and after each PAS protocol. TEP recruitment input-output curves revealed a generalized depression of TEPs in most ankle muscles of both legs after both PAS protocols that coincided with an increased gain only after transcortical-transspinal PAS. Transcortical-transspinal PAS increased and transspinal-transcortical PAS decreased the low-frequency-dependent TEP depression, whereas neither PAS protocol affected the TEP depression observed upon paired transspinal stimuli. These findings support the notion that transspinal and transcortical PAS has the ability to alter concomitantly cortical and spinal synaptic activity. Transspinal and transcortical PAS may contribute to the development of rehabilitation strategies in people with bilateral increased motoneuronal excitability due to cortical or spinal lesions.